Dinamika Respon Mitigasi Petani Padi di Jawa Barat dalam Menghadapi Dampak Perubahan Iklim serta Kaitannya dengan Pendapatan Usaha Tani - Elly Rasmikayati; Bobby Rachmat Saefudin; Dini Rochdiani; Ronnie Susman Natawidjaja (Department of Urban and Regional Planning, Diponegoro University, 2020)
Paddy farming has been affected by climate change phenomena such as high rainfall and long dry seasons which have caused plant and crop failure. To minimize the impact of climate change on their farming, paddy farmers undertake various strategies for dynamically adapting to climate change. This study aimed to analyze and assess the dynamics of the mitigation response by paddy farmers in West Java to minimize the impact of climate change. The object of research was paddy farmers in West Java. The research sample was selected using a multi-stage cluster random sampling technique to collect 300 respondents. Data analysis methods used descriptive statistics and multivariate analysis of variance (manova). The results showed that paddy farmers in West Java have dynamically mitigated climate change along with climate change over time. Types of climate change mitigation response applied by the majority of paddy farmers in West Java included planting shading trees, using energy saving technologies, cultivating organic agriculture, planting different crops instead of rice, changing farming to animal husbandry, migrating, looking for other income sources outside farming and renting/selling their land. Other mitigation responses that have rarely applied but interesting to explore were of shifting the planting and harvesting periods, selecting planting varieties, adapting plantation patterns and irrigation techniques. Farmers in Subang District who applied the most four types of climate change mitigation response earned higher income greater than those in Indramayu and Karawang.